Prosedur Penerbitan Surat Perintah Pengeluaran (SP2) Peti Kemas dalam Meningkatkan Efisiensi Layanan Depo pada PT. Prima Indonesia Logistik Belawan - Maria Christina Lumbanraja; Masringgit Marwiyah Nst (Pusat Riset dan Inovasi Nasional, 2025)
Procedure for Issuing a Container Release Order (SP2) in Improving Depot Service Efficiency at PT. Prima Indonesia Logistik Belawan / Maria Christina Lumbanraja / Nit.2201005 / Department of Commercial Shipping and Port Administration – Politeknik Adiguna Maritim Indonesia Medan 2025. The preparation of this paper is intended to conduct an in-depth study of the procedures for issuing Container Release Orders (SP2) and to assess their impact on the efficiency of depot services at PT. Prima Indonesia Logistics Belawan. The SP2 is a vital document that serves as official authorization to release containers from the depot to their final destination, and the issuance mechanism largely determines the smooth flow of logistics. In practice in the field, delays and inaccuracies in SP2 procedures often lead to long queues, operational congestion, and a decline in service quality. The author uses a qualitative approach through direct observation or field research, supplemented by library research to strengthen the analysis. The findings indicate that the biggest obstacles to SP2 issuance lie in the slow data verification process, limitations in digital systems, and weak coordination between departments. Therefore, improvements in operational standards, integration of information systems, and enhancement of human resource capacity through training are needed. With these improvements, the container release process is expected to be faster, more accurate, and capable of supporting smooth logistics distribution overall.